Constructing Causal Understanding in Complex Systems: Epistemic Strategies Used by Ecosystem Scientists. (5th June 2019) - Kamarainen, Amy M; Grotzer, Tina A
Abstract: Moving from a correlational to a causal account involves epistemological assumptions in any discipline. It presents particular challenges when phenomena involve multiple causes, time lags, feedback loops, or thresholds, as is the case in ecosystem science. Although reductionist approaches may contribute to explanatory efforts, investigation in ecosystems science requires a systems perspective. Understanding how ecosystem scientists arrive at causal accounts—and importantly, that they do—is critical to public understanding of science. Interviews with ten ecosystem scientists revealed the strategies and habits of mind that ecosystem scientists bring to examining complex systems. The scientists described challenges in conducting experiments at relevant scales and the epistemic strategies employed in response. The themes included constructing a body of evidence using multiple approaches, integrating results through statistical and process-based models, measuring and describing variability, conducting experiments in context, thinking across levels, considering the limits to generalizability, and exercising epistemic fluency. We discuss implications for K–20 education.